Pengembangan LKPD Fisika Berbasis Contextual Teaching and Learning pada Materi Elastisitas dan Hukum Hooke untuk Peserta Didik Kelas XI di SMA Negeri 2 Bantul - Nurtanti Yutia; Yosaphat Sumardi; Daimul Hasanah (Jurnal Ilmiah Profesi Guru (JIPG), 2021)
This study aims to produce a physics student worksheet (LKPD) based on Contextual Teaching and Learning (CTL) about elasticity and Hooke's law for class XI students at SMA N 2 Bantul, to find out learning materials and sources and to find out students' attitudes towards LKPD. The research is Research and Development (R&D) which was developed by Sugiyono. Data collection techniques by observation, interviews and questionnaires. Data analysis used descriptive statistics. Validator states LKPD Very Good and reads Very Good. Student responses indicate that the LKPD is very good and good. Thus, the LKPD is worthy of being used as learning and teaching materials.